Estudo da seletividade neuronal à orientação e frequência espacial no wulst visual da coruja suindara (Tyto alba): dinâmica de surgimento e separabilidade interdimensional - Claudiana Souza de Amorim (2016)
The visual system of barn owl has been the target of numerous studies along the years. The visual wulst is a telencephalic region that receives thalamic afferents and which has certain functional analogy to the mammals primary visual cortex. Studies of the 70s of the last century showed that wulst neurons are selective to the orientation, but few studies have been carried out investigating such property. Likewise, the spatial frequency (SF) selectivity had not been investigated more thoroughly. In the present study, we investigated selectivity orientation and spatial frequency selectivity, its temporal dynamics and the relationship between these two dimensions by reverse correlation technique. A total of 63 cells were isolated in 5 sedated barn owls (Tyto alba), using standard techniques of extracellular records. The stimuli used were sinusoidal gratings varying in orientation (n = 12, 15º steps), spatial frequency (n = 6-8, 1 octave steps) and phase (n = 8 or 4, 45º or 90º steps). The orientation tuning curves were fitted by a function von Mises and the spatial frequency tuning curves by a modified Gaussian (Priebe et al., 2006) and these curves parameters such as bandwidth and preferred orientation and SF were extracted. The wulst neurons are highly selective for orientation and spatial frequency, and such selectivity are heterogeneous. The mean bandwidths found are: 26,78º and 2.54 octaves. Temporal dynamics were characterized for both selectivity and they rapidly emerged (around 30 - 43 msec) and their duration vary from cell to cell. These selectivities emerge probably due to excitatory thalamic processes, and in addition, there is evidence of intra-wulst inhibitory mechanisms, especially those related to non-optimal stimuli. There is an inseparability of the two dimensions, i.e. the orientation selectivity is influenced by spatial frequency, so that the cells become more selective as frequency increases. Further investigations are needed to better understanding about the inhibitory mechanisms related to the emergence of these selectivities.